Preliminary investigation of the nutritional composition of two commercial fish species: Rainbow trout (Oncorhynchus mykiss) and Atlantic salmon (Salmo salar) - Kocatepe, D; Turan, H; Köstekli, B; Altan, CO; Çorapci, B (Journal of the Hellenic Veterinary Medical Society, 2023)
In this study, it was aimed to compare of nutritional composition, cholesterol, trans fatty acids, fatty acids, lipid quality index, vitamins (A, B9, B2, B12, D3), selenium (Se), and iron (Fe) contents between farmed Atlantic salmon and rainbow trout. Crude protein, crude fat, carbohydrate, and energy values of Atlantic salmon were slightly higher than rainbow trout while crude ash and moisture values were higher in rainbow trout (p < 0.05). The cholesterol content of samples in rainbow trout and Atlantic salmon were found as 77.37±1.07 mg 100g-1 and 99.45±2.72 mg 100g-1, respectively (p<0.05). Trans fatty acids of both species were found as <0.3 g 100g-1. ƩSFA value of rainbow trout was found higher than the Atlantic salmon, on the other hand, the ƩMUFA values were found higher in the Atlantic salmon (p<0.05). However, the ƩPUFA values were found similar for both fish species (p>0.05). In general, the results show that rainbow trout contains two times more EPA+DHA amount than Atlantic salmon. While vitamin A has been found higher in rainbow trout, other vitamins (B9, B2, B12, D3) have been higher in Atlantic salmon (p<0.05). Additionally, iron (Fe) and selenium (Se) contents in rainbow trout has been significantly higher than Atlantic salmon (p<0.05). TRANSLATE with x <input id="LanguageMenu_svid" style="display: none;" onclick="this.select()" type="text" name="LanguageMenu_svid" value="en" /> <input id="LanguageMenu_textid" style="display: none;" onclick="this.select()" type="text" name="LanguageMenu_textid" /> <span id="__LanguageMenu_header" class="DDStyle" onclick="return LanguageMenu && !LanguageMenu.Show('__LanguageMenu_popup', event);" onkeydown="return LanguageMenu && !LanguageMenu.Show('__LanguageMenu_popup', event);">English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian TRANSLATE with COPY THE URL BELOW <input id="ShareTextbox" onclick="this.select()" type="text" name="ShareTextbox" readonly="readonly" /> <!--a id="TwitterLink" title="Share on Twitter"> <a-- id="FacebookLink" title="Share on Facebook"> </a--> Back <input id="EmailSubject" type="hidden" name="EmailSubject" value="Check out this page in {0} translated from {1}" /> <input id="EmailBody" type="hidden" name="EmailBody" value="Translated: {0}%0d%0aOriginal: {1}%0d%0a%0d%0aAutomatic translation powered by Microsoft® Translator%0d%0ahttp://www.bing.com/translator?ref=MSTWidget" /> <input id="ShareHelpText" type="hidden" value="This link allows visitors to launch this page and automatically translate it to {0}." /> EMBED THE SNIPPET BELOW IN YOUR SITE <input id="EmbedSnippetTextBox" onclick="this.select()" type="text" name="EmbedSnippetTextBox" value=" " readonly="readonly" /> Enable collaborative features and customize widget: Bing Webmaster Portal Back